(untitled) (Bangladesh Critical Care Journal, 2014)
Electroencephalographic monitoring provides dynamic information about the brain function that permits early detection of changes in neurologic status, which is especially useful when the clinical examination is limited. Identification of ongoing electrographic seizures, non-convulsive status epilepticus (NCSE), periodic epileptogenic discharges (PED), irreversible cerebral dysfunction i.e., isoelectric tracing would help the care providers in appropriate decision making regarding the management. Non-convulsive seizures (NCSz) are more common than previously recognized and are associated with worse outcome if not treated in time. Majority of seizures at the ICU are not clinically identified because of the disease phenomena or as the patient may remain under sedation. Studies revealed the first NCSz within 1 to 24 hours of EEG monitoring; longer period of monitoring is required in comatose patient and those with PED. Factors associated with an increased risk of NCSz and NCSE include coma, prior clinical seizures, CNS infection, trauma, stroke, hypoxic ischemic encephalopathy, brain tumor, recent neurosurgery, and PED. In resource-poor situation, EEG is frequently requested to confirm brain death, particularly where there is limited information on neurological examination or inconclusive apnea test; or when the patient is in prolonged state of coma. Presence of isoelectric tracing for at least 30 minutes in the EEG along with other clinical evidences is helpful in such situations. Extreme care should be taken for recording and reviewing continuous EEG (cEEG) monitoring at the ICU where sources of electrical noise are present. Patients identified with electrographic seizures and mild to moderate degree encephalopathy, with presence of normal background activities had better outcome compared to those with PED, monorrhythmic alpha beta coma and severe generalized encephalopathy. Real-time detection of ischemia at a reversible state is technologically feasible with cEEG and should be developed into a practical form for prevention of in-hospital infarction. Brain function monitoring with EEG is useful and this is in great demand at the ICU of present time. Such monitoring can help to improve neurological outcome in a variety of ICU settings. DOI: http://dx.doi.org/10.3329/bccj.v2i1.19954 Bangladesh Crit Care J March 2014; 2 (1): 28-34